Factor influencing English language apprehension among employees in Management Services and Human Resources Division of Royal Malaysian Customs Department Putrajaya / Anis Asyikin Mohd Yahya - Mohd Yahya, Anis Asyikin (Faculty of Business and Management, 2020)
Most companies and organizations, including those which use English as a formal language, profit from the ability to communicate in English. Organizations doing international business would definitely employ people who speak English in the first or second language on a regular basis, rendering it very important for them to use English on the job. Therefore, this study is intended to investigate factor influencing English language apprehension among employees in Management Services and Human Resources Division of Royal Malaysian Customs Department Putrajaya. The dependent variable in this study was factor of English language apprehension whereas four factors composed of the independent variables, namely education and knowledge, communication anxiety and self-esteem. The Census Method was used as a Complete Enumeration Survey Method the respondents collected total of 104 from Management Services and Human Resources Division of Royal Malaysian Customs Department. The Statistical Package for Social Sciences Software (SPSS) was used to key all data collected in and interpret them. The data were gathered to evaluate the descriptive, correlation and multiple regression. To check the interaction between variables, a multiple regression approach has been used. The result indicates that education and knowledge have significant relationship with factor of English language apprehension. The most significant predictor of English language apprehension is education and knowledge which found that the lower education and knowledge the higher apprehension of English language. The finding of this study can be very useful in preventing English language apprehension by various parties such as government, associations as well as businesses.